Влияние типа и размера расчетных сеток на точность расчета течений в вихрекамерных нагнетателях - Сёмин, Дмитрий Александрович; Роговой, Андрей Сергеевич (НТУ "ХПИ", 2016)
На основе численного расчета течений в вихрекамерном нагнетателе с помощью моделей URANS и DES произведено исследование влияния типа и размера расчетных сеток на точность расчета. Получено, что погрешность расчета перестает меняться при числе элементов более 6 млн. Для модели DES это значение больше в два раза. При использовании детальной сетки целесообразней использовать тетрагональную сетку.

On the basis of numerical calculation of fluid flow in vortex chamber supercharger by means of models URANS and DES research of grids type and size influence on accuracy of computation is made. It is received that the calculation error ceases to change at number of elements more than 6 million For DES method this value in 2 times is more. At flow modelling in vortex chamber supercharger with a detailed grid, owing to more difficult construction hexagonal grids, it is more expedient to use a tetragonal grid in the absence of special distinctions in an error. The estimation of errors is made by comparison with the integrated parameters of a flows received experimentally. As a result of comparison on kinematics parameters, such as distribution of pressure to a end cover of the vortex chamber is received that all considered models give about an identical error.
Influence of grids type and size on accuracy of fluid flow computation in vortex chamber superchargers
Keywords: погрешность расчета; верификация; интегральные параметры; расчетная сетка; calculation error; verification; integrated parameters